2016
DOI: 10.1016/j.pec.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Communicating information concerning potential medication harms and benefits: What gist do numbers convey?

Abstract: Objectives: Fuzzy trace theory was used to examine the effect of information concerning medication benefits and side-effects on willingness to use a hypothetical medication.Methods: Participants (N=999) were recruited via Amazon Mechanical Turk. Using 3 x 5 experimental research design, each participant viewed information about medication side effects in 1 of 3 formats and information about medication benefits in 1 of 5 formats. For both sideeffects and benefits, one format presented only non-numeric informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Measures used to assess these variables were used in a previous study. 24 Results from that study support the construct validity of the measures.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Measures used to assess these variables were used in a previous study. 24 Results from that study support the construct validity of the measures.…”
Section: Methodsmentioning
confidence: 59%
“…24 Briefly, FTT is a dual process model of memory reasoning and development. It suggests that when individuals are exposed to a meaningful stimulus, they encode two types of representations in memory: a specific verbatim representation that captures the exact words/numbers conveyed and one or more gist representations that capture the essential bottom line meaning of the information.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Presenting quantitative information on treatment effects has become a standard requirement for evidence-based health information and decision aids because probabilities on the benefits and harms support realistic expectations and allow patients to weigh the pros and cons [ 18 ]. Furthermore, words have been shown to be unsuitable to express probabilities in several studies [ 19 , 20 ]. Instead, it might be necessary to provide readers with a clear statement on what a specific type of uncertainty means in order to aid interpretation.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 39 , 40 Research by Blalock and colleagues has also demonstrated that numeric risk information of side-effects may enhance decision making and also increase the willingness to take the medications. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Recent research conducted by Blalock and colleagues reported that non-numeric (words-only) information on side-effect risk conveys that medication can cause harm and thus decreases willingness to use the medication. 17 Despite the inconsistencies in interpretations with words-only descriptors, pharmacists mostly use vague words-only descriptions in their counseling sessions with patients. 18 , 19 Words-only descriptions seem to be advantageous because they are more natural to use and better appeal to a person’s emotional interests.…”
Section: Introductionmentioning
confidence: 99%